2021
DOI: 10.1371/journal.pone.0249088
|View full text |Cite|
|
Sign up to set email alerts
|

Research using population-based administration data integrated with longitudinal data in child protection settings: A systematic review

Abstract: Introduction Over the past decade there has been a marked growth in the use of linked population administrative data for child protection research. This is the first systematic review of studies to report on research design and statistical methods used where population-based administrative data is integrated with longitudinal data in child protection settings. Methods The systematic review was conducted according to Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) statement. The ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 128 publications
(284 reference statements)
0
8
0
Order By: Relevance
“…Overall, many studies did not report sufficient detail relating to data linkage processes (including consent procedures, quality of linkage, risk of bias, and technical considerations) to align with current guidance (e.g. Benchimol et al, 2015 ; Gilbert et al, 2018 ), which is consistent with the findings from Chikwava and colleagues’ recent review ( 2021 ). Understanding data quality is particularly important in assessing the value of data linkage as a method of studying child maltreatment, and the inadequate reporting of linkage processes make it difficult to assess the quality and potential biases of linkages and therefore the robustness of study conclusions.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Overall, many studies did not report sufficient detail relating to data linkage processes (including consent procedures, quality of linkage, risk of bias, and technical considerations) to align with current guidance (e.g. Benchimol et al, 2015 ; Gilbert et al, 2018 ), which is consistent with the findings from Chikwava and colleagues’ recent review ( 2021 ). Understanding data quality is particularly important in assessing the value of data linkage as a method of studying child maltreatment, and the inadequate reporting of linkage processes make it difficult to assess the quality and potential biases of linkages and therefore the robustness of study conclusions.…”
Section: Discussionmentioning
confidence: 57%
“…During this process, researchers set a threshold in order to balance missed and false matches, though choosing an ‘optimal’ threshold is often not straightforward ( Harron et al, 2017 ). Whilst there is established guidance for how to report on studies using (linked) administrative data, including the RECORD Statement ( Benchimol et al, 2015 ) and GUILD guidance ( Gilbert et al, 2018 ), a recent review of studies using administrative data linked with longitudinal data from child protection settings found that only three of the thirty included studies reported data linkage processes in enough detail to adequately conform with the recommendations of these guidelines ( Chikwava et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of routinely collected population-level administrative data for research provides the opportunity to study cohorts of populations that are hard to reach or considered high risk [38]. This study analyzed administrative records held within the Secure Anonymised Information Linkage (SAIL) Databank [39][40][41] for a cohort of mothers involved in public family law court proceedings and a matched group of mothers in the general population of Wales.…”
Section: Objectivesmentioning
confidence: 99%
“…The homelessness definition which extends beyond the literal definition of rough sleeping or rooflessness to the different forms, which include housing where there is no security or tenure and where the risk of ending up on the streets is high [14]. The multiple linked datasets provided background and personal characteristics associated with homelessness [50,51] and the large sample size allowed for more accurate prediction of estimates.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, it is also important to improve the evidence base for interventions that address mental health and homelessness issues that would result in improved outcomes for both Indigenous and non-Indigenous young people transitioning from care. Further research should ensure they use multiple data sources to augment or validate administrative data [50]. For instance, by conducting face-toface interviews where young people could use a life event calendar to document places they lived, including the duration or time spent in those housing conditions and their quality of life [42].…”
Section: Plos Onementioning
confidence: 99%